Tell me how it reads : tutoring deaf and hearing students in the writing center - Babcock, Rebecca Day, 1968- (Washington, DC : Gallaudet University Press, 2012)
"Deaf students are attending mainstream postsecondary institutions in increasing numbers, raising the stakes for the complicated and multifaceted task of tutoring deaf students at these schools. Common tutoring practices used with hearing students do not necessarily work for deaf people. Rebecca Day Babcock researched and wrote Tell Me How It Reads: Tutoring Deaf and Hearing Students in the Writing Center to supply writing instructors an effective set of methods for teaching Deaf and other students how to be better writers. Babcock's book is based on the resulting study of tutoring writing in the college context with both deaf and hearing students and their tutors. She describes in detail sessions between deaf students, hearing tutors, and the interpreters that help them communicate, using a variety of English or contact signing rather than ASL in the tutorials. These experiences illustrate the key differences between deaf-hearing and hearing-hearing tutorials and suggest ways to modify tutoring and tutor-training practices accordingly. Although this study describes methods for tutoring deaf students, its focus on students who learn differently can apply to teaching writing to Learning Disabled students, ESL students, and other students with different learning styles. Ultimately, the well-grounded theory analysis within Tell Me How It Reads provides a complete paradigm for tutoring in all writing centers."--Books.google.
Introduction -- The research context -- Literacy work in the tutoring session -- How tutoring gets done -- Interpersonal factors -- Tutoring a deaf student in the writing center.
Includes bibliographical references (pages 185-192) and index.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); English language -- Remedial teaching; Deaf people -- Education (Higher); Tutors and tutoring; Writing centers; Education, Higher; English language -- Remedial teaching; English language -- Rhetoric -- Study and teaching (Higher); Tutors and tutoring; Writing centers